Truly, madly, deeply : [large type] a novel - Kingsbury, Karen (Kingsbury, Karen. Baxter family., 2020)
"Eighteen-year-old Tommy Baxter wants to become a police officer. His mother, who lost her own father on September 11, objects, but Tommy's father, Luke, is proud of his son's decision. Tommy is also planning to ask his girlfriend, Annalee Miller, to marry him someday. However, she hasn't been feeling well--and tests reveal the unthinkable. While his girlfriend begins the fight of her life, Tommy is driven to learn more about the circumstances surrounding his birth and the grandfather he never knew. Secrets come to light that rock Tommy's world, and he becomes determined to spend his future fighting crime. Or is this just his way to a battle he cannot--the one facing Annalee?" --Page 4 of cover.